(untitled) (Rudarsko-geološko-naftni zbornik, 2025)
This study introduces a comprehensive methane gas risk analysis model applied for underground coal mines to assess explosion risks and promote sustainable occupational safety practices. The model calculates the methane risk score (%MRS) on a percentage scale, integrating three critical parameters: methane concentration (%C), ventilation performance (%V), and coal gas emission capacity (%G). A 30-day field study conducted in Turkey’s Soma region revealed %MRS values ranging from 15% to 38%, with the highest risks observed on days with elevated methane concentrations (0.66%), reduced ventilation performance (79.41%), and high gas emission capacity (20.38%). These findings validate the model’s capability to provide practical and reliable evaluations of combined risk factors. The modular structure of the model allows for recalibration to assess other hazards, such as dust explosions or roof collapses, and preliminary evaluations demonstrate its adaptability to regions with varying geological conditions and ventilation configurations. By offering a scalable and user-friendly approach, the model supports occupational safety professionals in implementing proactive measures, contributing to the sustainability of mining operations.